Effects of Coleus amboinicus L. Essential Oil and Ethanolic Extracts on Planktonic Cells and Biofilm Formation of Microsporum canis Isolated from Feline Dermatophytosis - Arpron Leesombun; Karnchanarat Thanapakdeechaikul; Jiraporn Suwannawiang; Pipada Mukto; Sivapong Sungpradit; Norasuthi Bangphoomi; Tanasak Changbunjong; Orathai Thongjuy; Thekhawet Weluwanarak; Sookruetai Boonmasawai (MDPI AG, 2022)
Microsporum canis is an important zoonotic fungus that causes dermatophytosis in domestic animals and their owners. Domestic cats are the primary reservoir for M. canis. Antifungal drugs frequently produce adverse effects on the host animal, increasing the demand for novel alternative treatments derived from nature. We evaluated the antifungal activity of Coleus amboinicus essential oil (CEO) and ethanolic extracts (CEE) against M. canis in planktonic and biofilm growth. Twelve clinical isolates of M. canis were identified in feline dermatophyte samples. Using GC-MS, 18 compounds were identified in CEO, with carvacrol being the major constituent. HPLC analysis of CEE revealed that it contained rosmarinic acid, apigenin, and caffeic acid. The planktonic growth of all M. canis isolates was inhibited by C. amboinicus extracts. The minimum inhibitory concentration at which ≥50% of the isolates were inhibited (MIC50) was 128 µg/mL (32-256 µg/mL) for both CEO and CEE. The MIC90 values of CEO and CEE were 128 and 256 µg/mL, respectively. CEO at MIC (128 µg/mL) and 2× MIC (256 µg/mL) significantly inhibited the biofilm formation of weak, moderate, and strong biofilm-producing M. canis. CEE at 2× MIC (256 µg/mL) significantly inhibited the biofilm formation of all isolates. Overall, C. amboinicus extracts inhibited planktonic growth and exhibited a significant antibiofilm effect against M. canis. Thus, C. amboinicus is a potential source of natural antifungal compounds.